2022
DOI: 10.3389/fmicb.2022.844856
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Microbial Eukaryotes Along the West Antarctic Peninsula in Austral Spring

Abstract: During a cruise from October to November 2019, along the West Antarctic Peninsula, between 64.32 and 68.37°S, we assessed the diversity and composition of the active microbial eukaryotic community within three size fractions: micro- (> 20 μm), nano- (20–5 μm), and pico-size fractions (5–0.2 μm). The communities and the environmental parameters displayed latitudinal gradients, and we observed a strong similarity in the microbial eukaryotic communities as well as the environmental parameters between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 110 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…To date, many surveys by metabarcoding have shown ciliate sequences in the pico-sized fraction (Romari and Vaulot, 2004;Wu et al, 2017;Xu et al, 2017;Grattepanche et al, 2022;Flegontova et al, 2023). Canals et al (2020) indicated that these sequences provided useful information about ciliate communities where over 94% of Ciliophora abundance from the Tara Ocean expedition in each size fraction corresponded to operational taxonomic units (OTUs) detected in the three fractions.…”
Section: Ciliate Sequences In Pico-sized Fractionmentioning
confidence: 99%
“…To date, many surveys by metabarcoding have shown ciliate sequences in the pico-sized fraction (Romari and Vaulot, 2004;Wu et al, 2017;Xu et al, 2017;Grattepanche et al, 2022;Flegontova et al, 2023). Canals et al (2020) indicated that these sequences provided useful information about ciliate communities where over 94% of Ciliophora abundance from the Tara Ocean expedition in each size fraction corresponded to operational taxonomic units (OTUs) detected in the three fractions.…”
Section: Ciliate Sequences In Pico-sized Fractionmentioning
confidence: 99%
“…Although polar oceans belong to one of the most productive and rapidly changing ecosystems on Earth 13 , the Southern Ocean remains poorly represented in these large surveys of marine protists. With the exception of a single small-scale study that examined protists in several deep-ocean water masses 14 , most studies of protists in the Southern Ocean focused on the photic layer [15][16][17][18][19][20][21] . Given the unique conditions during the polar winter, it is reasonable to assume that the heterotrophic lifestyle is of particular importance in the polar environment.…”
mentioning
confidence: 99%